Induction Motor Harmonics Voltage Waveform Analysis based on Machine Constriction - Karomah, Akhlaqul (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2020)
Abstractâ€” This paper discussed about harmonic analysis in an induction motor. Harmonics on induction motor appear due to the machine construction specially to its slots. The analysis of those harmonic will be one of the problems in the machine observation and design. In this paper a simulated computation of the flux magnet and emf induction voltage containing harmonic is proposed and discussed. FEMM simulation software is used and the result is compared to the mathematical analysis. The result shows that the emf induction harmonics wave derived from mathematic modelling and FEMM conform each other. Each of proposed methods can be used in the machine design or the evaluation analysis.Index Termsâ€”harmonic, induction motorÂ